2021
DOI: 10.1101/2021.06.01.444518
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Glucocorticoid receptor collaborates with pioneer factors and AP-1 to execute genome-wide regulation

Abstract: The glucocorticoid receptor (GR) regulates transcription through binding to specific DNA motifs, particularly at enhancers. While the motif to which it binds is constant across cell types, GR has cell type-specific binding at genomic loci, resulting in regulation of different genes. The presence of other bound transcription factors (TFs) is hypothesized to strongly influence where GR binds. Here, we addressed the roles of other TFs in the glucocorticoid response by comparing changes in GR binding and nascent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 98 publications
(157 reference statements)
1
4
0
Order By: Relevance
“…We found that GR-bound cis-regulatory loci newly synthesize unstable and lowly expressed non-coding RNAs, termed enhancer RNAs (eRNAs), in murine macrophages and livers [ 92 , 93 ]. Our profiles of eRNA expression from GR binding sites agree with reports from BEAS-2B epithelial cells stimulated with TNFα and Dexamethasone, and from A549 and U2OS cancer cell lines [ 94 , 95 ]. We found that GR-driven eRNA transcription occurred under physiological (liver in response to diurnal changes in glucocorticoid release) and inflammatory (activated macrophages) conditions.…”
Section: Discussionsupporting
confidence: 88%
“…We found that GR-bound cis-regulatory loci newly synthesize unstable and lowly expressed non-coding RNAs, termed enhancer RNAs (eRNAs), in murine macrophages and livers [ 92 , 93 ]. Our profiles of eRNA expression from GR binding sites agree with reports from BEAS-2B epithelial cells stimulated with TNFα and Dexamethasone, and from A549 and U2OS cancer cell lines [ 94 , 95 ]. We found that GR-driven eRNA transcription occurred under physiological (liver in response to diurnal changes in glucocorticoid release) and inflammatory (activated macrophages) conditions.…”
Section: Discussionsupporting
confidence: 88%
“…Outliers were removed to limit the y-axis range. b , c) The ratio between PRO-Seq reads per base pair in downstream introns UHP, DHP, or type 0 exons and the sum of these values for the corresponding gene, for every UHP, DHP, or type 0 exon, from the Wissink et al dataset (b) (45) and the Gupta et al dataset (c) (46). Outliers were removed to limit the y-axis range.…”
Section: Resultsmentioning
confidence: 99%
“…In order to estimate the difference in transcription speed of UHP and DHP exons compared to type 0 exons, we used two PRO-Seq datasets (45, 46) (Methods). These datasets sequenced nascent mRNA in addition to mature mRNA, and therefore allowed reads to be counted in the intronic parts of the nascent mRNA of each gene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We find GR and AP1 are conditionally dependent upon one another in their potential to activate local genes. A recent study suggests that both AP1 and CEBP act as pioneer factors that prime the genome for GR-induced transcription activation (Wissink et al 2021). We find all three of these factor families activate the initial wave of transcription changes, both in combination and in isolation.…”
Section: Discussionmentioning
confidence: 99%